Promising systems for controlling prosthetics: a review - A. M. Samandari (Омский научный вестник)
People with disabilities in the enormous scientific-technological revolution hope that it will overshadow the provision of assistance and find suitable solutions for them to lead their normal lives. The intersection of sciences among themselves took into account the problem of physical disabilities and, in particular, the loss of both upper and lower limbs. Modern prostheses are the product of the intersection of science and the technological revolution, which are still in the ladders of modernity and development due to they contain operators that can be controlled by brain signals according to the principle of neurainterfaces. Neuroimaging techniques such as electromyography, functional infrared spectroscopy and electroencephalography are the superior methods of controlling these modern prostheses can be modelled on two functions, namely independent work and hybrid work. In light of these data the article takes upon itself these systems in their individual and hybrid states. In addition, this article indicates which of these techniques is the most worthy in creating the preferred system. The scope of the research methodology limited to neuroimaging techniques towards scenarios of neurological rehabilitation and restoration of lost functions. The review has three axes. The first axis collects, summarizes and evaluates information from relevant studies published over the last decade. The second axis presents important results from previous experimental results in this field in relation to current research. This study was systematically conducted to provide a rich image and evidence-based evidence of prosthetic control techniques to all experts and scientists. The third axis is to identify a wide area of knowledge that requires further investigation, and follow-up the succession of scientific events of these systems towards the possibility of integration among themselves to create the most promising system for controlling prostheses.